Knowledge, Attitude, and Practice toward COVID-19 Questionnaire-Indonesian Version - Yafi Sabila Rosyad; Yohanes Andy Rias; Tiur Romatua Sitohang; Pasionista Vianitati; Pembronia Nona Fembi; Raden Surahmat; Nia Desriva (Media Keperawatan:Politeknik Kesehatan Makassar, 2021)
Coronavirus disease was detected for the first time since the extraordinary incident in Wuhan, China, in December 2019 and has now spread to 204 countries. COVID-19 is a highly contagious disease. This study aimed to translate the Knowledge, Attitude, and Practice toward COVID-19 Questionnaire and evaluate its validity and reliability Indonesia version. The original was Knowledge, Attitude, and Practice toward COVID-19 Questionnaire translated from English into Indonesian. The reliability scale analysis technique does validity and reliability testing. The question item validity is sawed from the magnitude of r-table value with r-count and reliability seen through Cronbach's alpha coefficiency. This study shows the Knowledge, Attitude, and Practice toward COVID-19 Questionnaire in the context of Indonesian all items of valid and reliable.